Implementasi Program MBKM Mandiri di SMA Negeri 2 Kupang: Pengembangan Bakat Musikal Siswa Melalui Kegiatan Paduan Suara oleh Mahasiswa Pendidikan Musik FKIP UNWIRA - Margaretha Maharani Bengan Boli; Maria Antonia Bare Aran; Tadeus Susanto Samsu; Afra Alan Jaur; Yohanis Devriezen Amasanan (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) program offers opportunities for students to enhance their competencies beyond campus. This article examines the implementation of the MBKM Mandiri program by Music Education students from Universitas Katolik Widya Mandira (UNWIRA) at SMA Negeri 2 Kupang, focusing on choir activities. These activities included planning, regular rehearsals, team building, and performances. The results showed increased student confidence, character development, and musical talent enhancement. For the students, the program provided practical experience that strengthened professional competencies and soft skills. This article highlights the challenges faced and the solutions implemented throughout the program. The implementation emphasizes the importance of collaboration between higher education institutions and schools in advancing education and arts.